Nuclear Icebreaker Feasibility Summary. - COAST GUARD WASHINGTON DC OFFICE OF ENGINEERING (1968)
The purpose of this document is to report on the final efforts of the feasibility study of a 35,000 SHP nuclear propelled polar icebreaker. Included are the following considerations: Feasibility evaluation of hull form utilizing a 'geosym' expansion of the M-13 diesel icebreaker design, including development of a body plan; Preliminary weight estimates for the nuclear icebreaker; Development of a conceptual general arrangement and inboard profile of the vessel; Development of a preliminary floodable length curve; Preliminary definition of hull structure, structural material and ice load criteria; Preliminary definition of command and control provisions, including bridge placement, conning station provisions, navigation systems and communications systems; Preliminary development of design complement, accomodations and outfit; Description of propulsion machinery design, including determination of plant rating, selection of reactor type and conceptual design, definition of fuel cycle, safety systems, environmental safeguards and shielding requirements; Description of selected steam plant, including propulsion transmission system, propulsion plant control, and ship service electrical generation and distribution system; Preliminary design of propellers and shafting; Development of speed-power estimates; Estimate of icebreaking capability; Machinery arrangements within the M-13 hull; Description of auxiliary machinery requirements; Preliminary definition of the ship's scientific suite; and Development of the ship cost estimate. (Author) Assisted by NUS Corp., Washington, D. C. Rept. no. NUS-369 and Hydronautics, Inc.